Virgil, Aeneid 3 : a commentary - Horsfall, Nicholas. (Mnemosyne, Supplements, 2006)
This is the first detailed commentary on Aeneid 3, being some three times the size of that by R.D.Williams(1962), and aimed at the scholarly public. It treats fully the thorny problem of book 3's place in the growth of the poem, matters of linguistic and textual interpretation, metre, prosody, grammar, lexicon and idiom, as well as Virgil's sources and the literary tradition in which he writes. Full attention is given to matters geographical and nautical. New critical approaches and recent developments in Virgilian studies have been taken into account, with more attention to their spirit than to their language. A text, with translation, and three indices are included.